(untitled) (Homoeopathy for All, 2026)
Urtica urens, a homeopathic remedy prepared from the annual nettle (urtica urens), is a plant distinct from the common nettle (Urtica dioica). It has long been used in homoeopathy for anaemia, rheumatism, gout, urticaria and for expelling stones from the kidneys. This article explores the therapeutic potential of Urtica urens in homeopathy, highlighting its key indications, mechanisms of action, and the benefits it offers in treating a variety of health conditions.